Church Politics and the Genocide in Rwanda - Longman, Timothy (Journal of religion in Africa, 2001)
Christian churches were deeply implicated in the 1994 genocide of ethnic Tutsi in Rwanda. Churches were a major site for massacres, and many Christians participated in the slaughter, including church personnel and lay leaders. Church involvement in the genocide can be explained in part because of the historic link between church and state and the acceptance of ethnic discrimination among church officials. In addition, just as political officials chose genocide as a means of reasserting their authority in the face of challenges from a democracy movement and civil war, struggles over power within Rwanda's Christian churches led some church leaders to accept the genocide as a means of eliminating challenges to their own authority within the churches.